54 Frail older patients have a greater improvement in physical quality of life than robust patients at one year following invasive treatment for non-st elevation acute coronary syndrome. (5th June 2017) - Sinclair, Hannah; Gu, Sophie Zhaotao; Batty, Jonathan; Beska, Benjamin; Verrasamy, Murugapathy; Ford, Gary; Qiu, Weiliang; Kunadian, Vijay
Abstract : Introduction: Frailty, a vulnerability to physiological stressors due to a decline in reserve with age, is common in older patients who present with non-ST elevation coronary syndrome (NSTEACS) and is associated with a disproportionately high morbidity and mortality. We aimed to determine how frailty influences physical quality of life (QoL) outcomes after invasive treatment for NSTEACS. Methods: From February 2013 to April 2015, 232 patients aged 75 years with NSTEACS were enrolled into a multicentre prospective observational study. Frailty was assessed using the Fried criteria, where a score of 0 is robust, 1 or 2 is pre-frail and 3 is frail. QoL was evaluated using the Short Form-36 (SF-36) questionnaire (license number QM033917) at baseline and 1 year follow-up. The norm-based Physical Component Score (PCS), an aggregated summary score of the 8 SF-36 subscales, is reported. Results: Mean age was 81±4 years, 60% were male and 88% received invasive treatment (percutaneous coronary intervention or coronary artery bypass grafting). At presentation, 39 (16.8%) patients were robust, 123 (53%) were pre-frail and 70 (30.2%) were frail. Increasing frailty was associated with decreased physical QoL at both baseline and 1 year (p<0.001 for both time points). Although all frailty groups saw an increase in mean PCS, this difference was only statistically significant in frail patients (robust: 42.4±11.4 to 44.3±12.4, p=0.372; pre-frail: 38.4±11.4 to 41.6±11.7, p=0.117; frail: 27.2±8.1 to 32.9±12.7, p=0.015). In addition, only frail patients who received invasive treatment saw this significant increase in PCS between baseline and 1 year, although numbers receiving medical therapy was low (Figure 1). Conclusion: Although frail older patients with NSTEACS have a poorer physical QoL overall, our data suggest frailty is associated with a similar or greater improvement from baseline QoL in those who receive invasive treatment.